2022
DOI: 10.3389/fpsyt.2022.853602
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Electroencephalography Microstates in Drug-Naïve, First-Episode Schizophrenia

Abstract: ObjectiveMicrostate analysis is a powerful tool to probe the brain functions, and changes in microstates under electroencephalography (EEG) have been repeatedly reported in patients with schizophrenia. This study aimed to investigate the dynamics of EEG microstates in drug-naïve, first-episode schizophrenia (FE-SCH) and to test the relationship between EEG microstates and clinical symptoms.MethodsResting-state EEG were recorded for 23 patients with FE-SCH and 23 healthy controls using a 64-channel cap. Three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…EEG studies in (awake) patients with schizophrenia used a four-microstate topography solution comparable to the solution in the data presented here. Their cross-sectional comparisons with healthy subjects observed the patients with schizophrenia to have decreased duration 41 , 57-61 and lower frequency of occurrence 59 , 62 , 63 in microstate D. Of note, these studies also observed in patients with schizophrenia prolonged duration 59 , 62-64 and higher frequency of occurrence 57-59 , 63 in microstate C. Thus, changes in quantifiers in microstates D and C occurred within repeated suppression EEG intervals with increasing exposure to anaesthesia in patients with subsequent POD (Supp + |POD + ) that resemble neural network features seen in awake patients experiencing schizophrenic episodes.…”
Section: Discussionmentioning
confidence: 99%
“…EEG studies in (awake) patients with schizophrenia used a four-microstate topography solution comparable to the solution in the data presented here. Their cross-sectional comparisons with healthy subjects observed the patients with schizophrenia to have decreased duration 41 , 57-61 and lower frequency of occurrence 59 , 62 , 63 in microstate D. Of note, these studies also observed in patients with schizophrenia prolonged duration 59 , 62-64 and higher frequency of occurrence 57-59 , 63 in microstate C. Thus, changes in quantifiers in microstates D and C occurred within repeated suppression EEG intervals with increasing exposure to anaesthesia in patients with subsequent POD (Supp + |POD + ) that resemble neural network features seen in awake patients experiencing schizophrenic episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have shown that the microstate indicators of patients with neurological and psychiatric diseases will change accordingly and may become potential biomarkers of certain types of diseases ( de Bock et al, 2020 ; Wang et al, 2021 ; Sun et al, 2022 ). Microstate analysis can also be used as one of the indicators of drug treatment effects in patients with certain diseases ( Serrano et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological basis of microstate C is still highly controversial, in the study of Britz et al (2010) , microstate C was considered to be part of the salience network, which mainly detected and responded to internal or external stimuli received by other brain networks. The salience network, which plays a key role in switching between central executive functions and default modes, can combine interoceptive information with emotional salience to form subjective representations of one’s own body ( Sun et al, 2022 ). As the “mediator” of the brain, the salience network plays an integral role in the processing of sensorimotor information, general cognition, and the coordination between emotion, pain, and body movement.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has found altered properties of EEG microstates in patients with schizophrenia (24)(25)(26). Such findings were interpreted as reflecting the brain network malfunction underlying the symptomatology of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%